Variability Studies of Different Seed Sources of Pinus wallichiana with Special Reference to Seed and Germination Characteristics - Rawat, Kirti; Tyagi, Monika; Nautiyal, S.; Kumar, Pankaj (Indian Forester, 2006)
Genetic parameters for five seed traits (length, width, thickness, weight, and volume) and percentage germination were studied in twenty seed sources of Pinus wallichiana, mostly from the states of Uttaranchal and Himachal Pradesh in two successive years 2002 and 2003. Values for variability and expected genetic gain were calculated for all individual characters. Seed weight and volume exhibited high genetic variability, heritability and genetic gain. Almost all the seed characteristics were found to be highly heritable at 5% level of significance. Heritability values were maximum for seed weight and minimum for seed length. Hence, heavy and large seeds have to be chosen for the good results. A correlation study showed that seed length, width, thickness, weight and volume were positively correlated with each other. Seed thickness had the highest direct effect on seed width. Germination characteristics were also found positively correlated with each other.